KNOWLEDGE, ATTITUDE, AND PRACTICE LEVEL ASSESSMENT REGARDING DIABETIC RETINOPATHY CARE AMONG SAUDI DIABETIC PATIENTS IN SAUDI ARABIA: A CROSS-SECTIONAL STUDY (CAHIERS MAGELLANES-NS, 2024)
Background: Diabetes mellitus is a highly prevalent disease in Saudi Arabia. This disease has a lot of macro and micro vascular complications; one of the most common microvascular complications is diabetic retinopathy and it is prevalent in Saudi Arabia as well. Furthermore, it can affect the quality of life dramatically by causing vision loss. Thus, it is crucial to determine the knowledge, attitude, and practice level of the Saudi diabetic population about this dangerous complication.Objectives: Our purpose is to determine the knowledge, attitude, and practice level of diabetic retinopathy care among diabetic patients in the Kingdom of Saudi Arabia.Methodology: This cross-sectional study was conducted in different regions of Saudi Arabia by using a validated verbal questionnaire obtained from the literature after modifying it to be in a self-administered online form. Saudi diabetic patients aged 18 years and older was included in the study. There was a minimum number of 377 participants depending on the sample size calculated by (Raosoft, Inc., Seattle, WA, USA). After the data is entered by "Microsoft Office Excel Software", it was analyzed statistically by the Statistical Package of Social Science Software (SPSS) Program, version 20 (IBM SPSS Statistics for Windows, Version 20.0. Armonk, NY: IBM Corp.).Results: There is 33.7% out of 599 of the participants demonstrated good knowledge about DR, 48.7% exhibited a negative attitude towards diabetic retinopathy care, 18.5% exhibited good practice patterns, while a larger proportion, 81.5% demonstrated poor practice.Conclusion: The present study showed that knowledge, attitudes, and practice of DR among Saudi patients with DM were less than desired and relatively lower than most of the mentioned studies inside and outside Saudi Arabia. Rigorous efforts are required to raise awareness of eye complications among diabetic patients.